Acute effects of (–)-gallocatechin gallate-rich green tea extract on the cerebral hemodynamic response of the prefrontal cortex in healthy humans - Cha, Jihyun; Kim, Hyung-Su; Kwon, Gusang; Cho, Si-Young; Kim, Jae-Myoung (Frontiers in Neuroergonomics, 2023)
Objective: The benefits of long-term consumption of green tea on the brain are well known. However, among many ingredients of green tea, the acute effects of (−)-gallocatechin gallate-rich green tea extract (GCG-GTE), have received comparatively less attention. Herein, we investigated the acute effects of oral ingestion of green tea with GCG-GTE, which contains close replicas of the ingredients of hot green tea, on task-dependent hemodynamics in the prefrontal cortex of healthy adult human brains. Methods: In this randomized, double-blind, placebo-controlled, parallel group trial, 35 healthy adults completed computerized cognitive tasks that demand activation of the prefrontal cortex at baseline and one hour after consumption of placebo and 900 mg of GCG-GTE extract supplement. During cognitive testing, hemodynamic responses (change in HbO2 concentration) in the prefrontal cortex were assessed using functional near-infrared spectroscopy (fNIRS). Results: In fNIRS data, significant group x session interactions were found in the left (p = .035) and right (p = .036) dorsolateral prefrontal cortex (DLPFC). In behavioral data, despite the numerical increase in the GCG-GTE group and the numerical decrease in the Placebo group, no significant differences were observed in the cognitive performance measure between the groups. Conclusion: The result suggests a single dose of orally administered GCG-GTE can reduce DLPFC activation in healthy humans even with increased task demand. GCG-GTE is a promising functional material that can affect neural efficacy to lower mental workload during cognitively demanding tasks. However, further studies are needed to verify this.